Maternal Protein Restriction in Two Successive Generations Impairs Mitochondrial Electron Coupling in the Progeny’s Brainstem of Wistar Rats From Both Sexes - Santana, David F.; Ferreira, Diorginis S.; Braz, Glauber Ruda F.; Sousa, Shirley M. S.; Silva, Tercya Lucidi de Araújo; Gomes, Dayane Aparecida; Fernandes, Mariana P.; Andrade-da-Costa, Belmira Lara; Lagranha, Claudia J. (Frontiers in Neuroscience, 2019)
Maternal protein deficiency during the critical development period of the progeny disturbs mitochondrial metabolism in the brainstem, which increases the risk of developing cardiovascular diseases in the first-generation (F1) offspring, but is unknown if this effect persists in the second-generation (F2) offspring. The study tested whether mitochondrial health and oxidative balance will be restored in F2 rats. Male and female rats were divided into six groups according to the diet fed to their mothers throughout gestation and lactation periods. These groups were: 1) normoprotein (NP) and 2) low-protein (LP) rats of the first filial generation (F1-NP and F1-LP, respectively) and 3) NP and 4) LP rats of the second filial generation (F2-NP and F2-LP, respectively). After weaning, all groups received commercial chow and a portion of each group was sacrificed on the 30th day of life for determination of mitochondrial and oxidative parameters. The remaining portion of the F1 group was mated at adulthood and fed an NP or LP diet during the periods of gestation and lactation, to produce progeny belonging to 5) F2R-NP and 6) F2R-LP group, respectively. Our results demonstrated that male F1-LP rats suffered mitochondrial impairment associated with an 89% higher production of reactive species (RS) and 137 % higher oxidative stress biomarkers, but that the oxidative stress was blunted in female F1-LP animals despite the antioxidant impairment. In the second generation following F0 malnutrition, brainstem antioxidant defenses were restored in the F2-LP group of both sexes. However, F2R-LP offspring, exposed to LP in the diets of the two preceding generations displayed a reactive species (RS) overproduction with a concomitant decrease in mitochondrial bioenergetics. Our findings demonstrate that nutritional stress during the reproductive life of the mother can negatively affect mitochondrial metabolism and oxidative balance in the brainstem of F1 progeny, but that restoration of a normal diet during the reproductive life of those individuals leads toward a mitochondrial recovery in their own (F2) progeny. Otherwise, if protein deprivation is continued from the F0 generation and into the F1 generation, the F2 progeny will exhibit no recovery, but instead will remain vulnerable to further oxidative damage.